The power of weak interests in financial reforms: Explaining the creation of a US consumer agency - Lisa Kastner (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2016)
Dodd-Frank, the US financial reform law passed in response to the 2008 financial crisis, established the Consumer Financial Protection Bureau (CFPB), a new federal regulator with the sole responsibility of protecting consumers from unfair, deceptive, or abusive practices. This decision marked the end of a highly politicized reform debate in the US Congress, involving lobbying from business associations and civil society groups, in which proponents of the new bureau would normally have been considered to be much weaker than its opponents. Paradoxically, an emerging civil society coalition successfully lobbied decision-makers and countered industry attempts to prevent industry capture. What explains the fact that rather weak and peripheral actors prevailed over more resourceful and dominant actors? The goal of this study is to examine and challenge questions of regulatory capture by concentrated industry interests in the reform debates in response to the credit crisis which originated in the US in 2007. The analysis suggests that for weak actors to prevail in policy conflicts over established, resource-rich opponents, they must undertake broad coalition-building among themselves and with influential elite allies outside and inside of Congress who share the same policy goals.
Keywords: 330; financial crisis; financial regulation; consumer protection; interest groups; lobbying